2018
DOI: 10.1186/s12984-018-0407-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noisy galvanic vestibular stimulation in community-dwelling elderly people: a randomised controlled trial

Abstract: BackgroundBalance disorders are a risk factor for falls in the elderly. Although noisy galvanic vestibular stimulation (nGVS) has been reported to improve balance in young people, randomised control trials targeting community-dwelling elderly people have not been conducted to date. We aimed to assess the influence of nGVS on COP sway in the open-eye standing posture among community-dwelling elderly people in a randomised controlled trial.MethodsA randomised controlled trial of 32 community-dwelling elderly peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 37 publications
3
53
0
Order By: Relevance
“…First, nGVS was performed only with one stimulus intensity of 0.4 mA. We have reported that 0.4 mA nGVS is suitable for reducing COP sway in healthy young people and community-dwelling elderly people (Inukai et al, 2018a(Inukai et al, ,b, 2020. In this study, the COP sway post status did not decrease even if 0.4 mA nGVS was performed with closed-eyes standing position on a foam rubber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, nGVS was performed only with one stimulus intensity of 0.4 mA. We have reported that 0.4 mA nGVS is suitable for reducing COP sway in healthy young people and community-dwelling elderly people (Inukai et al, 2018a(Inukai et al, ,b, 2020. In this study, the COP sway post status did not decrease even if 0.4 mA nGVS was performed with closed-eyes standing position on a foam rubber.…”
Section: Discussionmentioning
confidence: 99%
“…COP sway was measured for 30 s at 100 Hz in a standing position with legs together using a CFP400PA102RS (Leptrino, Nagano, Japan). Average COP sway path length, mediolateral (ML) mean velocity, and anteroposterior (AP) mean velocity were calculated (Inukai et al, 2018a(Inukai et al, ,b, 2020.…”
Section: Measurement Of Center Of Pressurementioning
confidence: 99%
“…Recently, several groups of researchers have demonstrated that the application of subthreshold stochastic vestibular stimulation (SVS), also known as noisy galvanic vestibular stimulation, is associated with improved balance control during standing and changes in walking patterns [13][14][15][16][17][18][19][20]. For example, SVS results in reduced postural sway length and velocity during eyes-open quiet standing in young and older adults [15,16] and during eyes-closed quiet standing in patients with bilateral vestibulopathy [13,17]. In addition, others found increased gait speed and changes in stride measures with SVS during treadmill and overground walking in healthy adults and patients with bilateral vestibulopathy [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The third experiment, by performing an identical protocol but with the electrodes placed so that the vestibular apparatus was not stimulated, excluded the possibility that the effects seen with nGVS were due to motor learning, arousal, attention, or physical tension due to stimulation, as no change in COP sway path length was seen in this condition. In their RCT, Inukai et al (2018a) found results in agreement with Inukai et al (2018b), as the older adults randomized to the low-intensity condition demonstrated significantly reduced COP path length, as well as anteroposterior and mediolateral mean COP velocities, whereas the sham stimulation group showed no changes.…”
Section: Functional Effects Of Ngvs On Balancementioning
confidence: 70%
“…In this Neuro Forum, we discuss six recent articles (Inukai et al 2018a(Inukai et al , 2018bIwasaki et al 2018;Keywan et al 2018;Temple et al 2018;Wuehr et al 2018) that have explored the effects of nGVS on balance and gait in humans. Second, we discuss the potential mechanisms of the observed effects and, based on the current state of the art, give recommendations and directions for future research on nGVS for the purpose of improving balance and gait.…”
Section: Introductionmentioning
confidence: 99%